Transthoracic echocardiography of the neonatal laboratory piglet - Schwarz, Stephan; Kalbitz, Miriam; Hummler, Helmut D.; Mendler, Marc R. (Frontiers in Pediatrics, 2019)
Background: Newborn piglets are commonly used in biomedical research. However, cardiovascular imaging of this species is quite challenging. For point of care diagnostics of heart function transthoracic echocardiography may be used, which appears to differ comparing newborn piglets with adult pigs. To date, there are few data or studies on the feasibility and quality of measurement of functional echocardiographic parameters in very small neonatal piglets. Objectives: To study the feasibility of transthoracic echocardiography in very small newborn piglets in supine position. Methods: In 44 anesthetized and intubated newborn piglets, positioned in supine position [age 32 h (12-44 h), weight 1,220 g (1,060-1,495 g), median (IQR)] transthoracic echocardiography was performed using a point of care ultrasound device (M-Turbo
CRIS-Team Scopus Importer:2020-12-21
Keywords: Hemodynamic monitoring; Neonatal transthoracic echocardiography; Piglets; Swine; Ventricular function